Switching Dynamics and Energy Storage Properties of Fluorite‐Structured Materials. Issue 1 (9th January 2023) - Ali, Faizan; Ali, Tarek; Abbas, Akmal; Lehninger, David; Iqbal, Muhammad Faisal; Fadhali, Mohammed M.; Shaaban, Ibrahim A.; Czernohorsky, Malte; Seidel, Konrad; Kämpfe, Thomas
Abstract : Fluorite‐Structured Materials Recently, ferroelectric and antiferroelectric fluorite‐structured materials (HfO2 and ZrO2 ) have gotten much attention for memory‐ and energy‐ related applications because of being suitable for CMOS compatibility and ultra‐low deposition thickness. In article 2200403, Faizan Ali, Muhammad Faisal Iqbal, and colleagues discuss the frequency‐dependent phase switching and energy storage properties of HfO2 ‐based thin films.